Additional distinct findings in three cases with Wolfram syndrome - Kabakuş, Nimet; Çitak Kurt, A. Neşe; Kurt, Abdullah; Yildirim, Hanifi; Yilmaz, Turgut; Akarsu, Saadet (My University, 2005)
[Abstract Not Available]
Keywords: insulin; neuroleptic agent; risperidone; vasopressin; adolescent; anemia; article; case report; child; depression; echography; female; human; hydronephrosis; laboratory test; male; neurogenic bladder; nuclear magnetic resonance imaging; patient monitoring; physical examination; short stature; symptomatology; urologic examination; Wolfram syndrome